Serum hepatitis B core-related antigen is more accurate than hepatitis B surface antigen to identify inactive carriers, regardless of hepatitis B virus genotype. (November 2017) - Riveiro-Barciela, M.; Bes, M.; Rodríguez-Frías, F.; Tabernero, D.; Ruiz, A.; Casillas, R.; Vidal-González, J.; Homs, M.; Nieto, L.; Sauleda, S.; Esteban, R.; Buti, M.
Abstract: Objectives: To investigate whether hepatitis B surface antigen (HBsAg) and hepatitis B core-related antigen (HBcrAg) levels are useful to identify inactive carriers among HBeAg-negative patients infected by different hepatitis B virus (HBV) genotypes. Methods: In all, 202 consecutive HBeAg-negative patients with chronic hepatitis B, 135 inactive carriers and 67 with HBV activity, were prospectively followed for 1 year. Results: In HBeAg-negative patients, HBsAg levels differed across the different genotypes (p <0.001). The highest levels were observed in genotypes F or H (4.2 ± 0.6 logIU/mL), followed by genotype E (3.4 ± 1.1 logIU/mL), genotype A (3.4 ± 0.8 logIU/mL), and the lowest in genotype D (2.7 ± 1.1 logIU/mL). Variations in HBsAg levels were similar in inactive carriers and patients with HBV activity. HBsAg <3 logIU/mL showed good performance for identifying genotype D inactive carriers: 76% of genotype D inactive carriers met this cut-off versus ≤31% for genotypes A, E, F or H. However, in patients with genotype A, HBsAg levels ≤3.7 logIU/mL better classified inactive carriers. The combination of a single measurement of HBcrAg ≤3 logU/mL plus HBV DNA ≤2000 IU/mL yielded a positive predictive value and diagnostic accuracy >85% in all HBV genotypes, except genotype H or F, with values of 62.5% and 72.7%, respectively, for the two parameters. Conclusions: HBsAg levels varied across genotypes in HBeAg-negative patients. HBsAg levels <3 logIU/mL were only useful for identifying genotype D inactive carriers. A single HBcrAg measurement ≤3 logU/mL plus HBV DNA ≤2000 IU/mL was highly accurate for identifying inactive carriers, regardless of their HBV genotype.